ANALISIS KESALAHAN PESERTA DIDIK DALAM PEMBELAJARAN DI SMP AL-KINDI PEKANBARU - Agus Salim Daulay; Maimunah Maimunah; Yenita Roza; Rosa Murwindra (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract Mistakes in solving math problems are common for students. Most teachers often do not pay attention to the types of mistakes made by students. The types of mistakes made by students can be one of the successful benchmarks of mathematics. This study aims to describe the types of problems of students in solving mathematics problems at Al-Kindi Middle School Pekanbaru. The research method used is descriptive research with a form of qualitative research. Data collection techniques used are tests and interview, data analysis techniques used descriptive qualitative and quantitative. Subjects in the study were 26 students and objects that answered tangent questions circle 5 questions. Based on the results of data analysis it can be concluded: students make fact errors 17%, concept errors 34%, principle errors 39% and operating errors 10%. The biggest type of error is a mistake in principle and concept. The implication is that teachers need to understand the concepts and principles when teaching, so the level of errors in solving problems is low. and to the next researchers, to be able to carry out further in-depth research to improve the quality of mathematics education in schools related to students' mistakes in solving tangent circle material questions. Keywords : error analysis, tangent circle.